2004
DOI: 10.1152/ajpgi.00309.2003
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical roles of different nitric oxide synthase isoforms in colonic injury

Abstract: Nitric oxide (NO) is a free radical that is largely produced by three isoforms of NO synthase (NOS): neuronal (nNOS), endothelial (eNOS), and inducible (iNOS). NO regulates numerous processes in the gastrointestinal tract; however, the overall role that NO plays in intestinal inflammation is unclear. NO is upregulated in both ulcerative colitis and Crohn's disease as well as in animal models of colitis. There have been conflicting reports on whether NO protects or exacerbates injury in colitis or is simply a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 54 publications
6
72
2
2
Order By: Relevance
“…The protective mechanisms exerted by nNOS in that study were not defined, and in contrast, our study indicates that nNOS does not play a significant role in the generation of the inflammatory response induced by TNBS in the mouse. The divergent results between this study and the work by Beck et al (2) likely reflect the different colitis models used.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…The protective mechanisms exerted by nNOS in that study were not defined, and in contrast, our study indicates that nNOS does not play a significant role in the generation of the inflammatory response induced by TNBS in the mouse. The divergent results between this study and the work by Beck et al (2) likely reflect the different colitis models used.…”
Section: Discussioncontrasting
confidence: 93%
“…These observations suggest colitis affects both NO-based neurotransmission and gastrointestinal motility (39,53). Beck et al (2) using the DSS colitis model, recently identified nNOS as playing an important role in that model, with the loss of nNOS expression resulting in more severe disease and increased mortality. The protective mechanisms exerted by nNOS in that study were not defined, and in contrast, our study indicates that nNOS does not play a significant role in the generation of the inflammatory response induced by TNBS in the mouse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,35,36 However, studies that involve the use of iNOS inhibitors have generated mixed information, with the inconsistencies largely stemming from the narrow window of selectivity and specificity toward iNOS of these inhibitors. 14,15 Exogenous NO-donors stimulate electrolyte secretion in guinea pig mucosa, but with the role of endogenous NO largely undetermined. 37 A study documented the curative effects of iNOS inhibition with the use of L-NIL on smoke-induced pulmonary emphysema and reversal of the deterioration associated with emphysema in the presence of the drug.…”
Section: Inhibition Of Cftr and Inos Activity Attenuates Diarrhea In mentioning
confidence: 99%